Increased anxiety-related behavior in mice following β-citronellol inhalation. Issue 1 (1st January 2020) - Ueno, Hiroshi; Shimada, Atsumi; Suemitsu, Shunsuke; Murakami, Shinji; Kitamura, Naoya; Wani, Kenta; Takahashi, Yu; Matsumoto, Yosuke; Okamoto, Motoi; Ishihara, Takeshi
ABSTRACT: β-Citronellol is a monoterpene alcohol found in essential oils of various aromatic plant species. The physiological effects of β-citronellol inhalation on the central nervous system remain unclear. We investigated the effects of β-citronellol inhalation on mouse behavior. First, we examined whether the odor of β-citronellol was attractive or repellent to mice. Then, following 30 minutes of β-citronellol inhalation, a series of behavioral tests (elevated plus maze, open field, Y-maze, tail suspension, and forced swim tests) were performed. Mice were neither attracted to nor repelled by β-citronellol. Mice that inhaled β-citronellol showed an increase in anxiety-like behavior in the elevated plus maze and open field tests. Performance in the Y-maze and forced swim tests was not affected. These results indicate that β-citronellol acts on the central nervous system of mice following inhalation and increases anxiety. Essential oils and cosmetics containing β-citronellol should be used with caution.